Immune reconstitution and survival of patients after allogeneic hematopoietic stem cell transplantation from older donors. Issue 1 (14th November 2022) - Jiang, Peiyao; Cai, Yu; Zhou, Xiao; Yang, Jun; Tong, Yin; Huang, Chongmei; Qiu, Huiying; Zhou, Kun; Xu, Xiaowei; Zhang, Ying; Niu, Jiahua; Shen, Chang; et al.
Abstract: Background: The impact of donor age on the immune reconstitution of patients with hematological malignancies who underwent hematopoietic cell transplantation (HCT) is unclear. Method: We retrospectively compared the outcomes of 381 patients who underwent allogeneic peripheral blood stem cell transplantation (PBSCT) from 308 donors under 50 years of age and 73 donors over 50 years of age. IVIG was regularly supplemented for patients in the first 3 months post‐HCT. Results: The counts of CD8+CD45RA+ naïve T cells were significantly lower in patients of the older donor group than in the younger donor group in the first year after PBSCT (190.6 cells/μl vs. 239.6 cells/μl, p = .018). Patients in the older donor group had significantly fewer CD19+ B cells on day +270 (123.4 cells/μl vs. 183.5 cells/μl, p = .021) and day +365 (169 cells/μl vs. 271.1 cells/μl, p = .01) after PBSCT. Serum IgA (.76 g/L vs. .97 g/L, p < .001) and IgM levels (.75 g/L vs. 1.04 g/L, p < .001) were significantly lower in patients in the older donor group from day +60 to +365 after PBSCT. The EBV reactivation rate within the first 3 months after PBSCT was significantly higher in patients in the older donor group (48.6% vs. 38.3%, p = .034). However, the incidences of CMV reactivation, II‐IV acute graft‐versus‐host disease (aGvHD), chronic GvHD (cGvHD), 3‐year relapse rate, 3‐year transplant‐related mortality (TRM) and 3‐year overall survival (OS) were not significantly different between the two groups. Conclusion: In conclusion, donors ≥50 years old were associated with inferior immune reconstitution and higher EBV reactivation in patients after PBSCT, but no change in OS.